Monday
March 27, 2017

Post a New Question

Posted by on .

(4.3 x 10^3)(2 x 10^-8)

  • Math - ,

    to do this, first we multiply the 1st terms or the number with no exponent (not the terms with 10 raised to an exponent). thus:
    4.3*2 = 8.6
    now we multiply the 2nd terms,, recall that if they have the same base (here, the base is 10) we can simply add the exponents:
    10^3 * 10^-8 = 10^(3-8) = 10^(-5)

    now multiplying the answers we got:
    8.6 * 10^(-5)

    hope this helps~ :)

  • Math - ,

    4.3*10^3 * 2*10^-8=

    4.3*2*10^3*10^-8=

    8.6*10^[3+(-8)]=

    8.6*10^(3-8)=

    8.6*10^-5=

    8.6/10^5=

    8.6/100,000=

    0.000086

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question